2004
DOI: 10.1007/s00381-004-0967-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications of ventriculosubgaleal shunts in infants and children

Abstract: We believe the benefits afforded by ventriculosubgaleal shunting significantly outweigh the risks of the procedure and greatly ease the burden of care for this select population of children. Based on the literature and our own experience, the complications from this procedure are not excessive or extraordinarily unique compared with other neurosurgical CSF diversion techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…the peritoneum and pleura. Another study [19] done on 170 patients found that VSG shunts were associated with complications such as infection (5.9%), intracranial haemorrhage (1.1%) and wound leakage (4.7%). Another study [20] (n = 32) looked into VSG shunt survival and complications.…”
Section: Discussionmentioning
confidence: 99%
“…the peritoneum and pleura. Another study [19] done on 170 patients found that VSG shunts were associated with complications such as infection (5.9%), intracranial haemorrhage (1.1%) and wound leakage (4.7%). Another study [20] (n = 32) looked into VSG shunt survival and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several other treatment modalities have been used to address PHH, such as ventriculosubgaleal shunt (VSGS), endoscopic third ventriculostomy, external ventricular drainage or immediate shunting [4,5,10,19,20,21,22]. VSGSs are often appealing because they obviate the need for placing hardware that is notorious for its infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, 6.5% of infants developed leaks, which is similar to that reported in other series. 9,20,28 We make a continual effort to reduce the incidence of leaks even further with such measures as emptying the subgaleal pocket prior to scalp closure, meticulous watertight skin closure, and avoidance of pressure on wounds by hats or respiratory devices.…”
Section: Specific Benefits and Risks Of The Vsgsmentioning
confidence: 99%
“…9,10,16,18,28 The severe neurological complications associated with IVH and PHH and the increasing survival rates of infants with extremely low birth weights necessitate a better understanding of the benefits and disadvantages associated with the reservoir and VSGS. In this study, a retrospective review of preterm infants treated for IVH and PHH at a single institution over a 14-year period was performed.…”
mentioning
confidence: 99%